Examining the satisfaction of students from the personalized business design course in the field of health, in Smart University of Medical Sciences, Tehran in 2022-2023 - Somayeh Rajabzadeh; Babak Sabet; Ata Pourabbasi; Seyed Mohammad Ebadirad (Mashhad University of Medical Sciences, 2024)
Background: Personalized business courses are an effective way to learn the basics of a business or industry. This study analyzed the effectiveness of the business course offered at Smart University of Medical Sciences.Method: This study evaluated the personalized business course using retrospective data to assess learner satisfaction. The course was delivered entirely online but was flexible in delivery. It was designed according to the ASSURE educational model, which emphasizes content presentation and personalization of the learning experience. The course was attended by 132 participants. In this study, the validity of the data collection instrument was confirmed by ten SMUMS faculty members, after which a preliminary study was conducted with 10 pilot samples, yielding a Cronbach coefficient of 96%. For the translation into Persian, the World Health Organization guide was used as a methodological model.Results: A total of 15 out of 18 participants from the Ministry of Science were satisfied with the course, as were 87 out of 107 participants from the Ministry of Health. Satisfaction with the course was higher among males than females, (84.6% versus 74.3%). The course was rated satisfactory by 81.4% of participants.Conclusion: Satisfaction with the course may lead to similar courses being offered in the future. This personalized business course was a great success. Participants were satisfied with the content they learned and the progress they made.